METHOD THE REMOVAL OF REMARKS FROM HARD TISSUE OF TEETH INLIFE - Zaytcev, A.; Nikolishin, A.; Koval, V.; Ivanicky, I. (World of Medicine and Biology, 2010)
In the article the results of electronic transmission microscopy of enamel of teeth of man are presented at its addition the own method the removal of remarks from hard tissue of teeth inlife.